Pelaksanaan Pelayanan Publik di Ekowisata Kebun Raya Mangrove Surabaya 1 - Natasyah Elsistyana Putri; Santoso, Daniel Pedro; Muhammad Hafidhul Anwar; Sahistya Nabila Prameswari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
This study aims to determine the implementation of public services in the Surabaya Mangrove Botanical Garden 1 through the application of public service dimensions. The method used is descriptive qualitative, namely a research method that aims to understand social phenomena in depth, data collection techniques using interviews and documentation with sources in data mining in the field, processing data from the field, making research reports. Qualitative research using the Theory of Public Service Dimensions used in research according to ZEITHAML. Parasuraman, Berry / et.al. (1990) there are 5 dimensions in public services, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of this study are that the implementation of public service dimensions can improve public services in the Mangrove Botanical Garden, where the 5 dimensions of public service above have been implemented well. Tangibles: service buildings, posters, and attractive facilities, reliability: officers provide education according to their fields, officers solve visitor problems quickly and efficiently, responsiveness: officers prioritize the interests of visitors and provide responsive responses to visitors, strict SOP assurance on processing facilities in Mangrove Ecotourism, and empathy: an employee in Mangrove Ecotourism communicates with everyone fairly, openly, and equally without distinguishing status, position, background, ethnicity, religion.. Keywords: Service, public, ecotourism, mangrove, Surabaya